TREES PHYSIOLOGICAL RESPONSES TO AIR POLLUTION IN TAMAN MARGASATWA RAGUNAN AND UI DEPOK CAMPUS - Diana Selvia Hamid; Ratna Yuliati; Afiatry Putrika (BIOTROPIA, 2022)
Air pollution is a common environmental problem. Planting trees can minimize the adverse effects of air pollution. Plants can absorb and accumulate air pollutants through stomata. Biochemical changes in the leaves will appear as a physiological response of plants to air pollution that can be known by calculating the APTI (Air Pollution Tolerance Index) value. This study aimed to analyze the differences in physiological responses of five tree species in Taman Margasatwa Ragunan (TMR) South Jakarta and Universitas Indonesia (UI) Depok Campus as well as to find out the proper tree species planted in areas with high levels of air pollution. The leaves of five species (Hevea brasiliensis, Manilkara kauki, Artocarpus heterophyllus, Ficus septica, and Mangifera indica) were used to examine the effect of air pollution. Biochemical parameters (relative water content, leaf extract pH, total chlorophyll content, and ascorbic acid content) were observed from each species. The value of each parameter was calculated into the APTI equation. H. brasiliensis, F. septica, and M. indica were categorized as moderately tolerant plants, M. kauki were included as intermediate plants, and A. heterophyllus was a sensitive plant to air pollution in both locations. The highest APTI values were observed in M. indica in both locations. Thus, the recommended species planted in a polluted area was M. indica.